Genetic variants and non-genetic factors associated with a high prevalence of vitamin D deficiency in full-term neonates in Malaysia - Lee, Siew-Siew; Ling, King-Hwa; Subramaniam, Raman; Tusimin, Maiza; Rahim, Kartini Farah; Loh, Su-Peng (Elsevier BV, 2024)
A high prevalence of vitamin D deficiency has been reported in Malaysian pregnant women, indicating that neonates at birth are at increased risk of vitamin D deficiency. Factors including low dietary vitamin D intake and single nucleotide polymorphisms in the vitamin D metabolism genes have been associated with this deficiency in the population. However, there was limited data available regarding the prevalence of neonatal vitamin D deficiency and the factors associated with it among neonates in Malaysia. Therefore, this study aimed to determine the prevalence of vitamin D deficiency and explore the associations between maternal and neonatal gene polymorphisms, as well as non-genetic factors and neonatal vitamin D deficiency. A total of 217 mother-neonate dyads were recruited for this study. Data on skin type, maternal sun exposure, dietary intake, as well as maternal and neonatal 25-hydroxyvitamin D (25OHD) concentrations were collected. Maternal and neonatal vitamin D Receptor (VDR) SNP (rs2228570) and Group-specific component (GC) SNPs (rs4588 and rs7041) genotypes were determined using high-resolution melting (HRM) and restriction fragment length polymorphism, respectively. The results showed that 60.4%, 71.4% and 95.4% of neonates had cord blood 25OHD levels below 25 nmol/L, 30 nmol/L and 50 nmol/L, respectively. After adjusting for the maternal vitamin D status, the maternal VDR rs2228570 GG genotype was significantly associated with neonatal vitamin D deficiency (25OHD<30 nmol/L) (aOR = 2.63, 95% CI: 1.18–5.87, p = 0.018). Maternal vitamin D supplement intake was found to be a protective factor. However, maternal and neonatal vitamin D binding protein (VDBP) SNPs were not associated with neonatal vitamin D deficiency. The high prevalence of neonatal vitamin D deficiency reported in this study indicates the urgent need for the development and implementation of strategies to improve neonatal vitamin D status. The findings suggest that maternal supplementation may be an effective approach to enhance the vitamin D status of neonates.